Impact of Price Discounts on Consumer Buying Behavior in Kathmandu Valley - Gautam, Aditya (Nepalese Journal of Business, 2025)
This study examines the impact of price discounts on consumer buying behavior in Kathmandu Valley. Consumer buying behavior is the dependent variable. The selected independent variables are free samples, buy one get one free offer, loyalty discounts, cashback offers, and bundle discounts. The primary source of data is used to assess the opinions of respondents regarding free samples, buy one get one free offer, loyalty discounts, cashback offers, bundle discounts, and consumer buying behavior. The study is based on primary data from 126 respondents. To achieve the purpose of the study, a structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of price discounts on consumer buying behavior in Kathmandu Valley. The study showed a positive impact of free sample on consumer buying behavior. It indicates that provide free sample to the consumer leads to change in consumer buying behavior. Similarly, the study showed a positive impact of buy one get one free on consumer buying behavior. It indicates that offering buy one get one free to consumer leads to change in consumer buying behavior. Likewise, the study also revealed a positive impact of loyalty discounts on consumer buying behavior. It indicates that offering loyalty discounts may influence consumers’ purchasing decisions. Further, the study observed a positive impact of cashback offers on consumer buying behavior. It indicates that providing cashback offers may lead to changes in consumer purchasing behavior. In addition, the study observed a positive impact of bundle discounts on consumer buying behavior. It indicates that offering bundle discounts to consumers lead to influence the consumers’ buying behavior.